Cardiorespiratory responses and specificity of effectiveperformance in dance and pairsof dancers - Igor Soronovych; Andrii Diachenko; Georgiy Korobeynikov; Lesia Korobeinikova; Vladimir Raximov (Фізична реабілітація та рекреаційно-оздоровчі технології, 2025)
Purpose. The aim of the study: to identify the model characteristics of the functional reserve of elite dancers taking into account cardio-respiratory reactions.